HUBUNGAN FAKTOR INDIVIDU DAN FAKTOR PEKERJAAN TERHADAP STRES KERJA PADA KARYAWAN ENGINEERING AND DESIGN SECTION DI PT CILEGON FABRICATORS TAHUN 2021 - Alya Azzahra Utomo (2022)
Workers still have to stay active during the COVID-19 pandemic and encounter many stressful situations. Problems faced by workers such as long working hours, excessive workloads, and short rest periods. Work stress has consequences on a person's physical and mental health. The purpose of this study was to analyze the association between individual and occupational factors with occupational stress. The method was quantitative analytic with a cross-sectional design. The subjects were all employees of the Engineering and Design Section at PT Cilegon Fabricators with a total of 66 people using the total sampling method. The statistical test used is Chi-Square test. The results showed that interpersonal relationships at work (p-value = 0.014) had a significant association with occupational stress. The POR value is 5.5, which means that employees with poor interpersonal relationships are 5.5 times more likely to experience occupational stress than employees with good interpersonal relationships. Age (p-value = 0.321), education level (p-value = 0.191), marital status (p-value = 0.716), years of service (p-value = 0.557), and workload (p-value = 1,000) had no association with occupational stress. Therefore, workers are advised to build good communication by listening and providing feedback in order to improve interpersonal relationships at work.